Prosthetic Status in Relation to Weight Status and Occupation among Parkinson’s Disease Patients in Baghdad-Iraq - Al-Taweel, Ali F; Qasim, Alhan A (Journal of Baghdad College of Dentistry, 2018)
Background: The symptoms of Parkinson’s disease (PD) can lead to problems in movement and coordination that lead to difficulty in maintaining well oral cleaning which can then negatively affect dental status of those Patients. The aim of present study: To evaluate prosthetic status in relation to weight status and occupation by age and gender among Parkinson’s disease Patients in Baghdad-Iraq. Methods: The sample consisted of 104 patients with Parkinson disease attended to the Neurosciences Hospital in Baghdad city / Iraq, aged 60-79 years Prosthetic Status was recorded according to WHO(1997). Weight status was recorded according to Trowbridge 1988 and occupation was recorded according to Erikson and Goldthorpe (1992) and Ganzeboom et al (1989). Results: The subjects without prosthesis tend to be more from any prosthesis type followed by partial denture and bridge, all types of prosthesis found to be decreased with increasing of age in both arches except combination of bridge and partial denture and complete denture were found to be increased with increasing of age with statistically highly significant association between age and prosthesis in upper arch. Males were found to have more prosthesis than females but with statistically no significant association. The subjects without any prosthesis, both bridge and partial denture types in upper arch found more in normal weight than the over and obese ones, while the combination of bridge and partial denture with complete denture tend to have slightly more in over weight with highly significant association. In lower arch other two prosthesis categories tend to be more in overweight subjects than other their counterparts with equally distributed of partial denture between normal and obese ones whose this prosthesis tend to be more than the overweight ones with statistically significant association. The with+ without+ self-employees category tends to have no prosthesis, partial denture and bridge prostheses more than other their counterparts with approximately equally distributed of other prosthesis categories but with statistically no significant association in upper arch while in lower arch the percentage of subjects with free prosthesis was found in with+ without+ self-employees category, while the partial denture and bridge found to be more in with+ without+ self-employees and upper grade professional but these findings tend to be statistically no significant association. Conclusion: Age, gender, occupation and weight have an effect on prevalent of prosthetic status of Parkinsonâ€™s disease patients. This may be due to difference in previous oral hygiene, health awareness, severity of Parkinsonâ€™s disease and difference in income status between them.